PERSPECTIVES OF FORMATION MARITIME LOGISTIC CLUSTERS IN GEORGIA - Kavtaradze, Medea; Revutska, Nataliia; Bejanidze, Natia (European Scientific Journal, ESJ, 2016)
The purpose of this research is to estimate the prospects and possibilities of establishing maritime logistics clusters in Georgia. Cluster forms of activities, particularly maritime logistic clusters, have been the object of the study in this article. The main method of the research is a comparative analysis of the advantages and limitations of cluster forming and functioning of maritime logistics. Development of maritime logistics clusters, in the article, is considered as using of transport industry potential through the development of logistics processes for the creation of additional value. Sea ports are considered as important links in the logistics chain. Creation of maritime cluster was studied in the article on the basis of Batumi and Poti Sea Ports, what should increase the competitiveness of both the port and other companies - cluster members. Creating a cluster provides synergies and new opportunities for innovative handling of technological operations in port logistics. The implementation of the logistics cluster business model based on the Batumi Sea Port should facilitate the involvement of industry, transport and logistics companies in the impact zone of the port logistics. The result of the maritime logistics cluster operation should strengthen the position of Batumi Sea Port in Georgia, both in the terms of transit goods maintenance and in the economic development of country as well. The paper contains the main prerequisites for the forming and functioning of maritime logistics cluster in Batumi and Poti Sea Ports: significant untapped potential in marine, cargo storage and air cargo logistics; completion of GeorgiaTurkey railway will open new possibilities in efficient transportation. In the article was concluded that marine and railway development will stimulate road transport and logistics centers development. Development of transport system will significantly improve competitiveness of Georgian products in price.